2001
DOI: 10.1302/0301-620x.83b5.0830640
|View full text |Cite
|
Sign up to set email alerts
|

Thermal capsular shrinkage for shoulder instability

Abstract: We present the short-and medium-term clinical results of thermal shrinkage in selected groups of patients with multidirectional or capsular stretch-type instability. We treated 56 patients (61 shoulders) by laser-assisted capsular shrinkage (LACS) and 34 patients (38 shoulders) by radiofrequency (RF) capsular shrinkage. The two groups were followed for mean periods of 40 months and 23 months, respectively.In the LACS group the mean Walch-Duplay score improved to 90 points 18 months after the operation, but the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
36
0
2

Year Published

2003
2003
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 15 publications
3
36
0
2
Order By: Relevance
“…Initially, it was thought that thermal capsular shrinkage would be particularly useful for MDI because of the ability of this procedure to decrease capsular volume globally. Most authors have found an increased risk of failure with thermal capsular shrinkage for treatment of MDI ranging from 24% to 59% [43] [2,27,57,69]. We noted a failure incidence of 28% (eight of 26) for MDI in our series.…”
Section: Discussionsupporting
confidence: 46%
See 2 more Smart Citations
“…Initially, it was thought that thermal capsular shrinkage would be particularly useful for MDI because of the ability of this procedure to decrease capsular volume globally. Most authors have found an increased risk of failure with thermal capsular shrinkage for treatment of MDI ranging from 24% to 59% [43] [2,27,57,69]. We noted a failure incidence of 28% (eight of 26) for MDI in our series.…”
Section: Discussionsupporting
confidence: 46%
“…Outcomes of thermal capsular shrinkage in contact athletes and in shoulders with a history of previous dislocations have been less satisfactory than open and other arthroscopic stabilization procedures for the most part [2,13,16,21,43,61,65,69]. Our results for thermal capsular shrinkage in contact athletes were poor with 31% failure, and in shoulders with a history of previous dislocations, 26% failed.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Posttraumatische oder habituelle Instabilitäten von Gelenken sind oft für Patienten und Operateure gleichermaßen ein schwieriges Problem [15,19]. Ins- [19].…”
Section: Kapselschrumpfung An Der Schulterunclassified
“…Ins- [19]. Die Rezidivrate ist insgesamt jedoch deutlich höher als die Literaturangaben nach offen-chirurgischem anterioren Kapselshift (10-15%).…”
Section: Kapselschrumpfung An Der Schulterunclassified